2018
DOI: 10.1038/s41467-018-03290-0
|View full text |Cite
|
Sign up to set email alerts
|

All-optical control and super-resolution imaging of quantum emitters in layered materials

Abstract: Layered van der Waals materials are emerging as compelling two-dimensional platforms for nanophotonics, polaritonics, valleytronics and spintronics, and have the potential to transform applications in sensing, imaging and quantum information processing. Among these, hexagonal boron nitride (hBN) is known to host ultra-bright, room-temperature quantum emitters, whose nature is yet to be fully understood. Here we present a set of measurements that give unique insight into the photophysical properties and level s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 37 publications
2
66
0
Order By: Relevance
“…A threshold of 160 meV is very close to that expected based on the Herzberg-Teller effect, but as SPE persists for excitation at much higher energies than this, it has been concluded that both direct and indirect excitations are responsible for the polarization changes 34 . The existence of a fast decaying intermediate and a long-lived metastable state accessible from the first excited electronic state has also been proposed in another recent study 63 . Indirect absorption mechanisms supporting misalignment of emission and absorption dipoles has been envisaged in another recent study 62 .…”
Section: Absorption and Emission Dipole Polarisationmentioning
confidence: 77%
“…A threshold of 160 meV is very close to that expected based on the Herzberg-Teller effect, but as SPE persists for excitation at much higher energies than this, it has been concluded that both direct and indirect excitations are responsible for the polarization changes 34 . The existence of a fast decaying intermediate and a long-lived metastable state accessible from the first excited electronic state has also been proposed in another recent study 63 . Indirect absorption mechanisms supporting misalignment of emission and absorption dipoles has been envisaged in another recent study 62 .…”
Section: Absorption and Emission Dipole Polarisationmentioning
confidence: 77%
“…A newer report from the same group presented more experimental and theoretical data to confirm this finding. The report of Kianinia et al presents a study of several quantum emitters with the PL and two‐laser repump technique, noticing that some of the studied cases can be attributed to various vacancy‐related defects . A sharp 4.09 eV line with two replicas separated by 0.18 eV and a broader 5.3 eV line were reported in Ref.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, in the field of synthetic structures, a full integration between the labels and the materials, for example super-resolution autofluorescent materials, is desirable. To this aim, first reports using conjugated polymers [43][44][45][46][47] , fluorescent nanodiamonds 148,149 or synthetic polymers that incorporate fluorescent units in the main backbones pave the way towards material-dye integration.…”
Section: [H1] Conclusion and Perspectivesmentioning
confidence: 99%